Peningkatan Hasil Belajar Mengoper Bola Pada Permainan Sepak Bola Menggunakan Model Pembelajaran Kooperatif Tipe TGT Siswa SMA Negeri 2 Bone - Andi Amry Yahya; Haeril Haeril; Wis Eko Prayogi; Nurjamal Nurjamal (Phsyical Education Health and Recreation Department of STKIP-YPUP Makassar, 2021)
This research is classroom action research (Classroom Action Research). Aims to find out the learning outcomes of passing students of SMA Negeri 2 Bone with the TGT (Team Games Tournament) learning model. By using the sample method in this research, there are 19 students in class XI. The results of this study show that there is a significant effect on learning to pass the ball using the TGT Learning model. This can be seen from the initial conditions, there are still many students who get scores below the KKM, which is 75%. Then further classroom action research was conducted with 2 cycles in the first cycle, from 19 students there were 9 students still in the incomplete category with a percentage of 47.37% and there were 10 students in the complete category with a percentage of 52.63%. Then in the second cycle of 19 students there were 2 students still in the incomplete category with a percentage of 10.53% of students and as many as 17 students in the complete category with a percentage of 89.47%. From this comparison, it proves that there is an increase in the mastery of student learning outcomes from the first cycle is 52.63% completeness with 10 subjects who reach the KKM to the second cycle, namely 89.47% completeness with the number of students who reach the KKM as many as 17 students. The achievement of mastery student learning outcomes can be categorized into a satisfactory category so that the TGT type cooperative learning model provides changes to aspects of the ability to pass the ball for class XI students of SMA Negeri 2 Bone.